Determinan Penanaman Modal Asing Langsung di Indonesia Periode Tahun 2016-2020 - Sudirman Sudirman; Nurwafa Wafia (Al-Buhuts, 2023)
This study aims to examine the effect of gross domestic product, infrastructure, exports, and corruption perception index on foreign direct investment in Indonesia. The data used is time series data over a period of 25 years, namely from 2016-2021. The type of data is secondary data obtained from the Central Bureau of Statistics and Transparency International. The data is processed using multiple regression analysis method with the help of SPSS software version 26. The results of this study indicate that together the variables of Gross Domestic Product, Corrosion Perception Index, Exports, and Infrastructure have a significant effect on Foreign Direct Investment in Indonesia. Then partially, the gross domestic product variable and the corruption perception index have a positive and significant effect on foreign direct investment. Likewise, the export variable has a positive but not significant effect on foreign direct investment in Indonesia. Meanwhile, infrastructure has a negative and significant effect on foreign direct investment in Indonesia Â